HOW TO INCREASE ACADEMIC FLOW IN MATH STUDY: THE INFLUENCE OF SELF EFFICACY, SOCIAL SUPPORT AND ACHIEVEMENT MOTIVATION - Rafiqah Yunalis; Rena Latifa (Prodi Bimbingan Konseling Universitas Negeri Manado, 2021)
Academic flow is one of the conditions that can improve student academic achievement. Flow is an experience where someone is deeply and pleasantly involved so that flow when students do activities related to the academic field such as taking classes in class and doing assignments is called academic flow. This study aims to determine how the influence of self-efficacy and social support both support from parents, teachers and classmate support as well as demographic factors (level of student interest) on the academic flow of high school students in Mathematics subject to moderation by achievement motivation. The sampling technique in this study was carried out by means of probability sampling with 304 students as respondents. The measuring instrument used is the FPQ scale (Flow Perceptions Questionnaire), GSES-12 (General Self-Efficacy Scale), SSS (The Student Social Support Scale) and QCM (The questionnaire on current motivation). Analysis of the data used in this study was the statistical technique of structural equating modeling using SPSS 23 and to test the construct validity using LISREL 8.7. The results show that there is a significant effect of self-efficacy, demographic factors (level of student interest) and there is no significant effect of social support (parent support, teacher support and classmate support) on the academic flow of high school students in Mathematics which is moderated by anxiety challenges. interest and probability of success as dimensions of achievement motivation.